Respiratory Muscle Stretching Toward Pulmonary Vital Capacity for Asthma Patient - Yunani, Yunani; Widiati, Amrih; Jamaluddin, M (Health Notions, 2017)
Asthma caused dyspnea because bronchospasme. Expiration rate and inspiration volume decrease, it will reduce pulmonary vital capacity. Asthma patient need exercise to improve pulmonary vital capacity. The exercise will strengthen and endurance respiratory muscles that can increase activity tolerance. The objective of the study was to know the effect of respiratory muscle stretching toward pulmonary vital capacity of asthma patient. These study used quantitative study with quasy experiment by using randomized pretest posttest design. Intervention group used respiratory muscle stretching and control group used deep breathing exercise. The sample was 15 respondents for intervention group and 15 respondents for control group. The instruments were spirometry and observation sheet. Data analysis used T paired test where T test was 0.005 for intervention group and 0.000 for control group  by hypothesis test with Î± 0.05. The mean difference between two groups used Mann Whitney test, where T test was 0.001.